ANALISIS SALURAN DRAINASE AKIBAT GENANGAN DI KECAMATAN ILIR TIMUR II KOTA PALEMBANG - Ayu Marlina; Reni Andayani; Zuul Fitriana Umari; Musaddad (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Tridinanti, 2023)
Changes in land use in an area greatly affect water absorption. Inundation occurred in Ilir Timur II Subdistrict, Palembang City due to lack of maintenance of drainage channels and changes in land conversion which was originally land into a water catchment area, now it is a concrete or residential area. During the rainy season, water will fill residents' spaces in the form of puddles and floods, which will continue to increase surface runoff in the area. The impact of the inundation is very disturbing and detrimental to various parties. The purpose of this study is to determine the peak discharge, analyze existing drainage, and plan a new secondary drainage design. The data used are primary data, namely channel length measurement data, channel slope, and existing channel dimension measurement data. While the secondary data used is in the form of 10-year rainfall data obtained from two rain posts, namely the rain post in Sako District and the rain post in Ilir Barat I District, as well as land use data in the Fruit Watershed of Palembang City covering an area of 1222.89 hectares. Then carry out an analysis of changes in land use currently and calculation of peak discharge to plan the dimensions of the new secondary drainage channel. The current peak discharge (Qp) calculation results in the studied area are 24.4 m3/s. For the calculation of channel dimensions, it is planned to have a rectangular cross-section with channel dimensions at sta 0.00 - 672.80 m, namely the channel dimension height is 4.5 m, the channel width is 4.5 m, and the guard height (f) is 0.30 m. From the results of analysis and calculations it is known that with the dimensions of the new drainage design there will be no runoff along the secondary canal. It is hoped that this can be a reference in planning the drainage rearrangement in Ilir Timur II District to reduce frequent inundation.